Tinjauan Yuridis tentang Diakonia dalam Gereja - Rikardus Jehaut (Jurnal Alternatif Wacana Ilmiah Interkultural, 2020)
This article focuses on juridical analysis of the ministry of charity (diakonia) in the light of Codex Iuris Canonici 1983 and some of magisterial teaching such as Deus caritas est and Intima Ecclesiae natura (on the church’s deepest nature). Relying heavily on these Church’s documents, this article seeks to offer canonical insights concerning four points of particular interest: first, the ministry of charity (diakonia) is a constitutive element of the Church’s mission and an indispensable expression of her very being; second, by baptism, all the faithful have the right and responsibilities to devote themselves personally to the service of charity; third, the exercise of the ministry of charity requires organization. The community of the faithful and every faithful has the right, ad normam iuris, to form charitable organisations or create foundations to fund concrete charitable initiatives; fourth, the ministry of charity is directly connected to the Episcopal ministry. Indeed, the bishop is the one primary responsible for that ministry. He has a role in supervising and coordinating works of charity. This article argues that in the area of ministry of charity, diocesan bishop play a pivotal role. He must show a concrete and visible commitment, ensuring that the ministry of charity is to be the chief concern of the particular Church, promoting communion and dialogue among the various agencies as well as keeping the